Inclusivity and Expert Knowledge: An Examination of Wikipedia Talk Pages and Reference Lists - Luyt, Brendan (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Wikipedia relies on expertise to arbitrate rival knowledge claims (Sundin 2011). In choosing experts, Wikipedians define the boundaries of acceptable comment on any given subject. Inclusivity becomes a matter of how the boundaries of expertise are drawn. In this presentation I examine these boundaries and their implications as revealed through the talk pages produced and sources used by those Wikipedians writing articles on Philippine history. Wikipédia se base sur l’expertise pour arbitrer les assertions contradictoires (Sundin, 2011). En choisissant les experts, la communauté définit ce qui constitue un commentaire acceptable sur un sujet donné. L’inclusivité devient un concept sur lequel repose l’identification des frontières de l’expertise. Dans cette communication, j’examine ces frontières et leurs effets tels que révélés dans les pages de discussion produites et les sources utilisées par la communauté pour la rédaction d’articles sur l’histoire des Philippines.